Effect of interdots electronic repulsion in the Majorana signature for a double dot interferometer - Ricco, L. S. [UNESP]; Marques, Y. [UNESP]; Dessotti, F. A. [UNESP]; De Souza, M. [UNESP]; Seridonio, A. C. [UNESP] (Elsevier, 2016)
We investigate theoretically the features of the Majorana hallmark in the presence of Coulomb repulsion between two quantum dots describing a spinless double dot interferometer, where one of the dots is strongly coupled to a Kitaev wire within the topological phase. Such a system has been originally proposed without Coulomb interaction in Dessotti et al. (2014 [16]). Our findings reveal that for dots in resonance, the ratio between the strength of Coulomb repulsion and the dot-wire coupling changes the width of the Majorana zero-bias peak for both Fano regimes studied, indicating thus that the electronic interdots correlation influences the Majorana state lifetime in the dot hybridized with the wire. Moreover, for the off-resonance case, the swap between the energy levels of the dots also modifies the width of the Majorana peak, which does not happen for the noninteracting case. The results obtained here can guide experimentalists that pursuit a way of revealing Majorana signatures.
Keywords: Double dot interferometer; Fano effect; Kitaev wire; Majorana bound states; Quantum dots